PENGARUH GREEN ACCOUNTING, ENVIRONMENTAL PERFORMANCE, MATERIAL FLOW COST ACCOUNTING (MFCA) DAN ENVIRONMENTAL DISCLOSURE TERHADAP SUSTAINABLE DEVELOPMENT GOALS (SDGS) - Farida; Suprianing Arum , Lingling (Kajian Bisnis Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2023)
The rapid development of the world industry triggers competition between companies to achieve their goals. This competition has an impact on the environment around the company. The purpose of this study was to examine the effect of Green Accounting, Environmental Performance, Material Flow Cost Accounting (MFCA) and Environmental Disclosure on the Sustainable Development Goals (SDGS). The population used is manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2017-2021. The sampling technique used purposive sampling, so that the sample totalled 45 observations (9 companies for 5 years). The analysis tool uses multiple linear regression. The results of the study show that green accounting is able to increase the SDGs, while environmental performance, MFCA has no influence on the SDGs. This research has implications for manufacturers who apply green accounting by incurring environmental costs that will help increase the company SDGs.